A new species of freshwater crab of the genus Himalayapotamon Pretzmann, 1966 (Decapoda, Brachyura: Potamidae: Potaminae) from Uttarakhand, northern India - Pati, S.k.; Singh, S. (Zootaxa, 2017)
A new species of potamid freshwater crab, Himalayapotamon garhwalense n. sp., is described from a stream near Khanda in Pauri Garhwal district of Uttarakhand, India. The new species is differentiated from all congeners by a suite of carapace and gonopod features, including the short, stout and conical G1 terminal joint with gradually tapered distal portion. Himalayapotamon Pretzmann, 1966, is now represented by 11 species including H. garhwalense n. sp. An identification key to the species in the genus is provided.